Evaluation of hardening soil parameters for finite element analysis - Tan, Yun You. (2010)
The proper evaluation of soil parameters is a very important part of any geotechnical design. As more engineers are now moving from the Mohr-Coulomb soil model to the more advanced Hardening soil model in finite element analysis, there is a need to establish a proper procedure to evaluate the soil parameters for this model. In this study, parameters for different geological formations in Singapore were evaluated based on results from consolidated drained and undrained triaxial compression tests. The geological formations included in this study are: marine clay in Kallang formation, residual soil of the Bukit Timah formation, silty clayey sand of the Old Alluvium and hard clay of Fort Canning Boulder Bed.